2022
DOI: 10.1098/rspb.2022.0963
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-mediated between-plant communication in Scots pine and the effects of elevated ozone

Abstract: Conifers are dominant tree species in boreal forests, but are susceptible to attack by bark beetles. Upon bark beetle attack, conifers release substantial quantities of volatile organic compounds known as herbivore-induced plant volatiles (HIPVs). Earlier studies of broadleaved plants have shown that HIPVs provide information to neighbouring plants, which may enhance their defences. However, the defence responses of HIPV-receiver plants have not been described for conifers. Here we advance knowledge of plant–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…In the current study, we found that net photosynthesis did not differ between herbivore‐damaged plants and plants exposed to herbivore‐induced volatiles straight after exposure to the treatments. Earlier studies reported increases in photosynthesis rate upon insect feeding, which supports our observations (Gutsche et al, 2009), but to our knowledge no previous work reported increase in net photosynthesis rate upon exposure to volatile cues, except for a recent study on conifers by Yu et al (2022).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we found that net photosynthesis did not differ between herbivore‐damaged plants and plants exposed to herbivore‐induced volatiles straight after exposure to the treatments. Earlier studies reported increases in photosynthesis rate upon insect feeding, which supports our observations (Gutsche et al, 2009), but to our knowledge no previous work reported increase in net photosynthesis rate upon exposure to volatile cues, except for a recent study on conifers by Yu et al (2022).…”
Section: Discussionsupporting
confidence: 91%
“…Under complex natural environmental conditions, the quantity and composition of HIPVs as well as the timing of their emission are affected by biotic factors (e.g., herbivore density, species and age) and abiotic factors (e.g., light, temperature, water availability, fertilisation, wind and ozone) (Becker et al, 2015; Gouinguené & Turlings, 2002; Holopainen & Gershenzon, 2010; Vosteen et al, 2020; Yu et al, 2022). Light is an important environmental factor affecting accumulation of secondary metabolites in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms, including plant pathogens, can also take advantage of similar strategies to manipulate stomatal aperture for their benefit by opening stomata for entry into plant tissues (Melotto et al, 2006;Turner & Graniti, 1969;Underwood et al, 2007). Emerging evidence also suggests that HIPVs can increase stomatal aperture of conifers, resulting in increases in net photosynthesis of receiver plants (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%